Hubungan Inisiasi Menyusui Dini (IMD) Dengan Pemberian Asi Eksklusif Di Puskesmas Sonomartani Kecamatan Kualuh Hulu Kabupaten Labuhan Batu Utara Tahun 2022 - Pratiwi Puji Lestari; Srilina Br Pinem; Febriana Sari; Lisa Putri Utami Damanik (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Early Breastfeeding Initiation is the process of allowing the baby to breastfeed on its own immediately after birth. This is nature and a gift from God that has been arranged for us. Doing it is also not difficult, it only takes about one to two hours. IMD must be carried out immediately at birth, without delaying weighing or measuring the baby. Babies should also not be cleaned, only dried except for their hands. This process must take place skin to skin between baby and mother. This research uses an analytical type of research with a retrospective research design. The research aims to determine the relationship between early initiation of breastfeeding (IMD) and exclusive breastfeeding at the Sonomartani Community Health Center. Based on the data in table 4.3, it can be seen that 5 respondents (38.5%) did not practice IMD but did not provide exclusive breastfeeding and 8 respondents (61.5%) did not practice IMD but did not provide exclusive breastfeeding. Carrying out IMD and providing exclusive breastfeeding was 21 respondents (95.5%). The statistical test results of the chi square test obtained a p value = 0.000, so it can be concluded that there is a significant relationship between Early Breastfeeding Initiation (IMD) and exclusive breastfeeding, namely Ha received. The importance of giving birth in a health service is to avoid sudden emergencies that can cause complications and to provide care according to procedures. This is in line with research by Norhana, Arifin and Yulidasari (2016) that mothers who give birth in health facilities are 15,167 times more likely to carry out IMD. Of the 20 respondents who successfully carried out IMD, 19 respondents (95%) were accompanied by their husbands and family when giving birth and 17 respondents (84%) of them succeeded in providing exclusive breastfeeding. Husband and family support play an important role in managing IMD and building maternal self-confidence. The relationship between early initiation of breastfeeding (IMD) and exclusive breastfeeding at the Sonomartani Community Health Center in 2022" with a total of 35 respondents and data processing that has been carried out using SPSS, it can be concluded that the chi square test value is p < 0.05, meaning that Ho is rejected and Ha is accepted: Based on the research results, the majority of respondents who carried out Early Breastfeeding Initiation (IMD) were 22 respondents (62.9%). Based on the research results, the majority who gave exclusive breastfeeding were 26 respondents (74.3%). Based on the research results, there is a relationship between carrying out IMD and providing exclusive breastfeeding. The statistical test results obtained a chi square test value (p < 0.05) with a value of 0.000.